Investigating the effect of grit trait on performance and success in Hungarian athlete’s sample - Apró, Annamária; Fejes, Nikoletta; Bandi, Szabolcs A.; Járai, Róbert (Frontiers in Psychology, 2024)
1) Background: The aim of the present study is to translate the Grit questionnaire into Hungarian and validate specifically within the context of sports. The second goal is to assess the questionnaireto assess the Grit questionnaire in Hungarian as a pilot study in the athlete population and to compare the grit trait with the coaches' athlete evaluation. (2) Methods: 269 athletes, including 40 national team players, took part in the study, with an average age of 18.17 years (SD = 5.51). For the preliminary assessment, the Cloninger Temperament and Character Questionnaire (TCI-RH) was used; the coaches' athlete evaluation was modeled on a talent map. (3) Results: The confirmatory factor analysis confirmed the fit of the two-factor structure, and the internal reliability of the questionnaire scales also proved to be adequate. 2. There is no relationship between adolescents' perceived grit and coach ratings. 3. The national team players achieved a higher grit score. (4) Conclusions: Based on the psychometric indicators, the validity and reliability of the questionnaire proved to be adequate. Therefore, it is applicable and useful for psychological practitioners and researchers in the Hungarian population within the context of sports.1 GPA is a system used in high schools and universities, mainly in the US, to measure a student's performance and academic achievement. GPA is calculated by converting grades or percentages you receive for an assignment (A, B, C etc) to a corresponding point on the GPA scale. Most high schools and universities report grades on a 4.0 scale.